Some Remarks on the Investigation of Traces of Transhumance in the Early Medieval Balkans - Takács, Miklós (Historical Studies on Central Europe, 2022)
The study analyses the issue of the archaeological investigation of transhumance on the Balkan Peninsula in the early phase of the Middle Ages. More precisely formulated, our main question is why is this branch of investigation almost totally absent from the archaeology of the given period and geographical region? In the first part of the study, we give a brief overview of the history of prior research, pointing to the fact that although investigations into transhumance were largely carried out in other branches of science (history, linguistics ethnology), they may have potential impacts on the evaluation of archaeological material. In the second part of the study the factors are enumerated which are—in the author’s opinion—responsible for the described situation. At the end of the study, a potential solution is formulated for the described situation. A change is required in the focal areas of the research, with emphasis not only on the problems connected with the issue of transhumance but also on transgressing analyses based on national historical narratives. This change will—hopefully—create positive results through the initiation of research projects focusing on the discovery and excavation of sites in mountainous areas possibly connected with transhumance.